Correlation between level of knowledge about dysmenorrhea with dysmenorrhea management behaviour in Sleman - Fitriahadi, Enny; Nerawati, Yuni (Journal of Health Technology Assessment in Midwifery, 2024)
Introduction: Adolescence is a period of development that begins with the maturity of the physical (sexual) organs so that later they are able to reproduce, including puberty in young women, namely menstruation. Most women feel pain during menstruation, even the presence of discomfort and even severe pain is what is often called menstrual pain dysmenorrhea. Knowledge and treatment of dysmenorrhea is needed by young girls, physical problems that may arise are a lack of personal hygiene (personal hygiene) so that it risks causing disease, therefore women also have a responsibility regarding personal hygiene to themselves. Preliminary study found that some female students did not know about dysmenorrhea. This study was to determine the relationship between knowledge about dysmenorrhea and behavior in handling dysmenorrhea in adolescents at school in Sleman. Methods: Analytical survey method with a cross sectional approach, taking samples by total sampling using a questionnaire. Results: The results of the research on the relationship between the level of knowledge of adolescent dysmenorrhea and the behavior of handling dysmenorrhea at school in Sleman. Paste lack of knowledge as many as 23 respondents (41.1%), The behavior of handling dysmenorrhea with the highest percentage is the behavior of handling dysmenorrhea with only 26 respondents (51%). Discussion, and Conclusion: The statistical test results showed a correlation coefficient of 0.426 so that it can be stated that there is a relationship between knowledge about dysmenorrhea and behavior in handling dysmenorrhea in young women at school in Sleman with a low closeness relationship. It is hoped that the school can provide facilities or facilities to increase young women's knowledge about dysmenorrhea by holding programs and being able to work with health facilities. 426 so that it can be stated that there is a relationship between knowledge about dysmenorrhea and the behavior of handling dysmenorrhea in young women at school in Sleman with a low closeness relationship. It is hoped that the school can provide facilities or facilities to increase young women's knowledge about dysmenorrhea by holding programs and being able to work with health facilities. 426 so that it can be stated that there is a relationship between knowledge about dysmenorrhea and the behavior of handling dysmenorrhea in young women at school in Sleman with a low closeness relationship. It is hoped that the school can provide facilities or facilities to increase young women's knowledge about dysmenorrhea by holding programs and being able to work with health facilities.